An input-dependent safety measure and fail-safe strategy for multicopters - Gen Cui; Guangxun Du; Quan Quan; Zhiyu Xi; Yang Liu; Kai-Yuan Cai (Artificial Intelligence and Autonomous Systems)
In order to prevent loss of control (LOC) accidents, the real-time safety measure problem is studied for multicopters. Unlike the existing work, this paper does not try to monitor the performance of the controllers by system states. In turn, the lumped disturbances of multicopters under off-nominal conditions on input are estimated to affect a proposed measure to show users whether a multicopter will be LOC. Firstly, a new degree of controllability (DoC) is proposed for multicopters subject to control constraints and off-nominal conditions. An input-dependent safety measure is then defined based on the new DoC to show the control performance for multicopters to ensure safety. Besides, the proposed measure is applied to a fail-safe strategy to guide the control decision of multicopter under off-nominal conditions. Finally, simulation and experimental results show the effectiveness of the proposed measure and fail-safe strategy.